Fulminant rhinocerebral mucormycosis in a patient with metabolic comorbidities: an unusual case report - Montiel Alfonso, Miguel Angel (2025)
Mucormycosis is a rare but fulminant invasive fungal infection caused by fungi of the order Mucorales. It primarily affects patients with risk factors such as diabetes mellitus, hematologic malignancies, solid organ or hematopoietic stem cell transplantation, and prolonged immunosuppressive therapy. Its various clinical forms include the rhino-cerebral presentation, one of the most aggressive, characterized by rapid local progression with involvement of orbital, neurological and vascular structures, and high lethality if not diagnosed and treated promptly. We present the case of a 53-year-old male patient with a history of poorly controlled type 2 diabetes mellitus, who sought medical attention due to severe headache, right periorbital edema, and diplopia that had been present for 72 hours. A computed tomography (CT) scan of the paranasal sinuses revealed occupation of the left sphenoid sinus, adjacent soft tissue thickening, and signs of bone erosion of the lamina papyracea. These findings prompted nasal endoscopy with tissue sampling for histopathological analysis, which confirmed the presence of broad, non-septate hyphae with right-angle branching, consistent with rhinocerebral mucormycosis. Systemic antifungal therapy with liposomal amphotericin B was initiated, and endoscopic surgical debridement of the affected tissues was performed. Despite a multidisciplinary approach and timely implementation of therapeutic measures, the patient experienced rapid neurological deterioration, with impaired consciousness, and died a few days after admission.  This case underscores the need for high index of clinical suspicion in patients with complicated rhinosinusitis and predisposing factors, as well as the urgency of diagnosis and treatment to improve prognosis.